2014
DOI: 10.1051/0004-6361/201323214
|View full text |Cite
|
Sign up to set email alerts
|

Two spotted and magnetic early B-type stars in the young open cluster NGC 2264 discovered by MOST and ESPaDOnS

Abstract: Star clusters are known as superb tools for understanding stellar evolution. In a quest for understanding the physical origin of magnetism and chemical peculiarity in about 7% of the massive main-sequence stars, we analysed two of the ten brightest members of the ∼10 Myr old Galactic open cluster NGC 2264, the early B-dwarfs HD 47887 and HD 47777. We find accurate rotation periods of 1.95 and 2.64 days, respectively, from MOST photometry. We obtained ESPaDOnS spectropolarimetric observations, through which we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 91 publications
3
43
0
Order By: Relevance
“…Were the spot at the equator, a more complex toroidal field would have to be involved. Rho Ophiuchi is not the first case of spotted B stars as spots have been identified in other B-early stars, e.g., two young B2 stars in NGC 2264 (Fossati et al 2014), as we observed before. In these two cases, the magnetic origin of the surface spots is inferred by means of spectropolarimetric observations, with magnetic fields of a few hundred Gauss in intensity and configurations as simple and double dipoles, respectively.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Were the spot at the equator, a more complex toroidal field would have to be involved. Rho Ophiuchi is not the first case of spotted B stars as spots have been identified in other B-early stars, e.g., two young B2 stars in NGC 2264 (Fossati et al 2014), as we observed before. In these two cases, the magnetic origin of the surface spots is inferred by means of spectropolarimetric observations, with magnetic fields of a few hundred Gauss in intensity and configurations as simple and double dipoles, respectively.…”
Section: Discussionsupporting
confidence: 60%
“…In these two cases, the magnetic origin of the surface spots is inferred by means of spectropolarimetric observations, with magnetic fields of a few hundred Gauss in intensity and configurations as simple and double dipoles, respectively. Fossati et al (2014) discuss the origin of such magnetic fields, preferring the hypothesis of a merging event during the star formation rather than a fossil origin. The relevance of ρ Ophiuchi in this context is that its close distance allows further detailed investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with an evolutionary age (see Table 3) that compares reasonably well with the age of the parent open cluster NGC 3293, 10.7 Myr (Lotkin & Matkin 1994). There is also reasonably good agreement between the spectroscopic distance of CPD −57 • 3509 (d spec = 2630 ± 370 pc) and the cluster distance of ∼2460 pc (Briquet et al 2013;Petit et al 2013;Alecian et al 2014;Neiner et al 2014;Fossati et al 2014Fossati et al , 2015aSikora et al 2015;Castro et al 2015, grey circles), and CPD −57 • 3509 (black dot). Error bars are 1σ uncertainties.…”
Section: Discussionsupporting
confidence: 53%
“…Two spotted and magnetic early B stars in the young open cluster of NGC 2264 have been discovered by Fossati et al (2014), namely HD 47887 and HD 47777. For HD 47887, there is a X-ray detection in Chandra with a flux of 6.03 × 10 −15 erg s −1 cm −2 , at a distance of 800 pc this means a X-ray luminosity of ∼ 4.2 × 10 29 erg s −1 , which is lower than that observed on average in ρ Oph A.…”
Section: Discussionmentioning
confidence: 99%